Food advertisements on television and eating habits in adolescents: a school-based study - Delfino, Leandro Dragueta [UNESP]; Tebar, William Rodrigues [UNESP]; Santos Silva, Diego Augusto; Staquecini Gil, Fernanda Caroline [UNESP]; Mota, Jorge; Destro Christofaro, Diego Giulliano [UNESP] (Revista De Saude Publica, 2020)
OBJECTIVE: To analyze the association of television food advertisements with eating habits in Brazilian adolescents. METHODS: The sample was composed of 1,011 adolescents, aged from 10-17 years. The influence of television food advertisements on eating habits, as well as food consumption and socioeconomic variables were assessed through questionnaires. A binary logistic regression was performed to assess the magnitude of the associations, adjusted for gender, age, socioeconomic status, and parental schooling. RESULTS: Of the sample, 83.3% (n = 843) reported food consumption while watching TV. Adolescents who do not consume food while watching TV had a higher weekly consumption of fruits (3.98, SD = 2.0 versus 3.39, SD = 2.1) and vegetables (4.1, SD = 2.2 versus 3.4, SD = 2.3). Adolescents that consume food while watching TV had higher weekly consumption of fried foods (3.1, SD = 2.0 versus 2.3, SD = 1.7), sweets (4.1, SD = 2.1 versus 3.3, SD = 2.1), soft drinks (3.2, SD = 2.1 versus 2.2, SD = 1.9), and snacks (2.3, SD = 2.0 versus 1.6, SD = 1.7). For 73,8% of the sample, food advertisements induce product consumerism, most commonly sweets and fast foods. Buying or asking to buy food after seeing it on the television was associated with fried foods (OR = 1.36, 95%CI = 1.03- 1.79), sweets (OR = 1.69, 95%CI = 1.30-2.18), and snacks (OR = 1.57, 95%CI = 1.12-2.22). CONCLUSION: Food advertisements were associated with greater consumption of fried foods, sweets, and snacks in adolescents, even after adjusting for confounding factors.
Keywords: Adolescent; Feeding Behavior; Food Publicity; Food and Nutrition Education